The relationship between problem gambling, spending on loot boxes, and loot box opening videos : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatu, New Zealand - Wilkins, Jed Taylor (Massey University, 2020)
Loot boxes are in-game purchases in video games where the content is unknown before opening and is randomised. The content can have high or low rarity and can provide advantages in-game, encouraging ongoing purchasing behaviours through increased desirability of content. Loot boxes within video games operate on Variable-Ratio reinforcement similar to legally defined gambling and are argued to meet the criteria for gambling. Evidence shows a positive association between problem gambling symptomology and spending on loot boxes. However, there may be other factors in the relationship, one of these being loot box opening videos (e.g., on YouTube or Twitch). To date, one study has investigated the possibility that loot box opening videos are associated with loot box spending, which has suggested that this relationship between watching loot box opening videos and loot box spending exists; therefore, it is important to explore the association between problem gambling, loot box spending, and loot box opening videos, and also establish the problem gambling and loot box spending relationship in a New Zealand sample. We recruited a cross-sectional New Zealand sample (𝘯 = 313), and 𝘢 𝘤𝘰𝘯𝘷𝘦𝘯𝘪𝘦𝘯𝘤𝘦 𝘴𝘢𝘮𝘱𝘭𝘦 (𝘯 = 118) and conducted a survey investigating the relationship between loot box spending, problem gambling symptomology, and frequency and time spent watching loot box opening videos. The results from the two samples were mixed. There were few significant effects in 𝘵𝘩𝘦 𝘤𝘰𝘯𝘷𝘦𝘯𝘪𝘦𝘯𝘤𝘦 𝘴𝘢𝘮𝘱𝘭𝘦; however, limitations (such as extremely low loot box spending) in 𝘵𝘩𝘦 𝘤𝘰𝘯𝘷𝘦𝘯𝘪𝘦𝘯𝘤𝘦 𝘴𝘢𝘮𝘱𝘭𝘦 suggest the findings from the cross-sectional New Zealand sample may be more valid. The results from the cross-sectional New Zealand sample revealed that higher problem gambling symptomology correlated significantly with higher loot box spending. Regression analyses showed that the interaction between problem gambling symptomology and time spent watching loot box opening videos explained a significant amount of variance in loot box spending, while the interaction between problem gambling symptomology and frequency of watching loot box opening videos did not. Results replicated previous research suggesting that people with higher problem gambling symptomology are spending more money on loot boxes. The results also suggest that the amount of time spent, not the frequency of, watching loot box opening videos in combination with problem gambling symptomology is associated with higher loot box spending. Further research is required to attempt to replicate the findings.
Keywords: 520599 Social and personality psychology not elsewhere classified